2013
DOI: 10.1177/1741143213494189
|View full text |Cite
|
Sign up to set email alerts
|

A Day in the Life of New Headteachers

Abstract: It is known that the work of headteachers is demanding. Observation, diaries and logs completed by headteachers show a relentless, complex and emotionally demanding workload. What can be learned about headship from how new headteachers spend their time, and perhaps as importantly, what can new headteachers themselves learn? This article draws upon data, including that derived from observation, from a small-scale qualitative study of new headteachers in large cities, funded by the English National College for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 23 publications
2
44
0
2
Order By: Relevance
“…By gaining new competences in school management and leadership, the teachers are given a chance to change their professional roles. The research results herein focused on changes in education and on head teachers, and show that school management is an emotionally demanding and time-consuming job, characterised by a high level of legal responsibility (Chaplain 2001;Barrett-Baxendale and Burton, 2009;Earley and Bubb, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…By gaining new competences in school management and leadership, the teachers are given a chance to change their professional roles. The research results herein focused on changes in education and on head teachers, and show that school management is an emotionally demanding and time-consuming job, characterised by a high level of legal responsibility (Chaplain 2001;Barrett-Baxendale and Burton, 2009;Earley and Bubb, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…A literatura sobre o diretor escolar tem focado a complexidade do cargo e as inúmeras e intrincadas transformações a que vem estando sujeito (Cattonar, 2006;Earley & Bubb, 2013;Horng, Klasik, & Loeb, 2009;O'Malley, Long, & King, 2015), intervindo na dimensão formal da escola, através da coordenação de estruturas e processos, de modo a alcançar as metas do seu Projeto Educativo, mas igualmente intervindo ao nível relacional, atentando às necessidades sentidas pelos professores na escola, o que depende da criação de culturas favoráveis a processos sustentadores de DP. O comprometimento, a visão estratégica e a capacidade de liderança do diretor escolar são facilitadores da promoção de processos de indução e de DP, os quais obedecem a variáveis pessoais e profissionais dos professores e a variáveis contextuais do ambiente político-social em que atuam.…”
Section: C U Lt U R a D E E S C O L A L I D E R A N ç A Pe Dag ó unclassified
“…Researchers have used shadowing approaches to examine how organisational actors apportion their time to different kinds of tasks. Earley & Bubb (2013) were able to develop a detailed understanding of how and why new headteachers divided their time between competing managerial, administrative and leadership tasks. In a similar vein, Vie (2010) was able to answer questions about how the work of middle managers is changing.…”
Section: Movement and Real Timementioning
confidence: 99%
“…When I couldn't find what I was looking for to explain my new insights to myself in the research methods literature, I started to look in wider and wider circles, including more and more disciplines. In Education (Wolcott, 1973;Polite, McClure & Rollie, 1997;Roan & Rooney, 2006;Earley & Bubb, 2013) and in Nursing studies (Vukic & Keddy, 2002;Fransden, 2010;Johansen & Forberg, 2011) I found glimpses of similarity with what I had done, but their natural acceptance that shadowing was a legitimate approach and descriptions of shadowing didn't help me, beyond reassuring me that shadowing was being conducted elsewhere. This extended review process also helped me to see that what I called shadowing was actually called different things in different literatures and that what other people called shadowing often wasn't the same as what I had done at all.…”
Section: Introductionmentioning
confidence: 99%